The balancing act: How public construction clients safeguard public values in a changing construction industry - Kuitert, Lizet (A+BE | Architecture and the Built Environment, 2021)
Public bodies acting in the construction industry have to deal with major transitional issues, such as globalization and urbanization, population ageing, climate change and digitalization. Moreover, the public domain, private parties and society are becoming increasingly interdependent. As a result, safeguarding public values in the built environment has become ever more complex. Public bodies face the challenge to adhere to collective public values while confronted with private and societal values of external partners. This means that they have to deal with value pluralism and value-conflicts. In research, scarce attention has been paid to providing guidance to practitioners for dealing with multi-value trade-offs in operational processes. Hence, this research provides a construction-sector specific operationalization and a network perspective to the field of public value research. This research highlights the important role to be played by public commissioning in terms of safeguarding public values. It consists of three qualitative studies that utilize a range of different methods, including interviews, observations and document analysis. By this the research provides a contemporary perspective through which to study and execute the safeguarding of public values by public clients in the transition towards network governance in the construction industry. The dynamics of the sector-specific value interests of public construction clients, the occurrence of value conflicts in commissioning, and the safeguarding processes within both internal and external commissioning are studied. The practical implications derived from the research were translated into a value dialogue tool that can be used by public construction clients to professionalize safeguarding in their daily practice.